FACTORS ASSOCIATED WITH BULLYING BEHAVIOUR IN ADOLESCENTS AGED 13-15 YEARS OLD - Hartati; Mikawati; Pratiwi, Rizky; Suryani; Sia'tang , Weni (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Bullying behavior is a form of negative aggressive behavior exhibited by individuals or groups of children, involving physical or psychological disturbances. This phenomenon frequently occurs in schools and other places where children interact and can develop in any social context where human interaction exists. This study aimed to identify factors associated with bullying behavior at SMP YP PGRI Disamakan Makassar. A quantitative approach was employed using a cross-sectional design in an analytical survey. The sample was selected using proportional stratified random sampling. Subject characteristics data were collected through questionnaires, and data analysis was performed using the Chi-Square test. The results revealed significant associations between self-control and bullying behavior (ρ = 0.000, α = 0.05), peer influence and bullying behavior (ρ = 0.000, α = 0.05), as well as social media usage and bullying behavior (ρ = 0.000, α = 0.05). The study concluded that self-control, peer influence, and social media usage significantly influence bullying behavior at SMP YP PGRI Disamakan Makassar. This study recommends that the school organize educational programs to raise students' awareness of the impacts of bullying behavior.